2013
DOI: 10.3109/08037051.2013.823760
|View full text |Cite
|
Sign up to set email alerts
|

Aortic pulse wave velocity and HeartSCORE: Improving cardiovascular risk stratification. A sub-analysis of the EDIVA (Estudo de DIstensibilidade VAscular) project

Abstract: The results clearly illustrate the benefits of integrating PWV in the risk assessment strategies, as advocated by HeartSCORE, insofar as it contributes to a better discriminative capacity of global cardiovascular risk, particularly in individuals with low or moderate cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Physiological measurements of vascular stiffness and vessel wall thickness serve as surrogate risk markers of future cardiovascular risk [10,11]. Well-established and widely used vascular measures are carotid intima-media thickness (cIMT), pulse wave velocity (PWV) and augmentation index (AIX) [12][13][14]. They measure different vascular properties in distinct parts of the arterial tree, but are not entirely independent of each other, and covary to some extent [15].…”
Section: Introductionmentioning
confidence: 99%
“…Physiological measurements of vascular stiffness and vessel wall thickness serve as surrogate risk markers of future cardiovascular risk [10,11]. Well-established and widely used vascular measures are carotid intima-media thickness (cIMT), pulse wave velocity (PWV) and augmentation index (AIX) [12][13][14]. They measure different vascular properties in distinct parts of the arterial tree, but are not entirely independent of each other, and covary to some extent [15].…”
Section: Introductionmentioning
confidence: 99%
“…Maldonado et al [23] found that PWV could be used to predict cardiovascular outcomes in a low-to-moderate cardiovascular risk population. Pereira et al [24] reported that the combination of PWV with HeartSCORE showed a better discriminative capacity of major cardiovascular events than HeartSCORE alone. To the best of our knowledge, our data first proved the predictive value of PWV in a high-risk CAD population undergoing PCI.…”
Section: Discussionmentioning
confidence: 99%
“…Large population based studies have demonstrated that arterial stiffness is a strong predictor of CVD or CV events not only in the general population, but also in patients with CVD. 14 15 16 …”
Section: Vascular Agingmentioning
confidence: 99%